2012
DOI: 10.1525/cond.2012.110103
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Assemblages of Feather Bacteria in Relation to Plumage Color in Female Great Tits

Abstract: Abstract. Microorganisms are known to play an important role in shaping the life histories of animals. Recent studies have proposed that the coloration of birds' plumage could reflect individual quality through associations with feather-degrading bacteria. however, few studies have explored such relationships. We studied breeding female great Tits (Parus major) during nest building and chick rearing to explore associations between bacteria inhabiting their yellow chest feathers and feather coloration. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Earlier studies have suggested that feather microorganisms could play a role in the evolution of feather colouration (Shawkey et al 2007;Shawkey et al 2009;Gunderson et al 2009;Kilgas et al 2012a). However, experimental evidence on free-living birds is still lacking to support this hypothesis (Clayton 1999;Cristol et al 2005;Gunderson 2008).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Earlier studies have suggested that feather microorganisms could play a role in the evolution of feather colouration (Shawkey et al 2007;Shawkey et al 2009;Gunderson et al 2009;Kilgas et al 2012a). However, experimental evidence on free-living birds is still lacking to support this hypothesis (Clayton 1999;Cristol et al 2005;Gunderson 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, carotenoid pigments invested in feather colouration are no longer available for immune system functioning (Olson & Owens 1998;Aguilera & Amat 2007; but see Navara & Hill 2003). If bacteria present on feathers interact with the host immune function, an allocation trade-off between immune response and feather colouration would lead to negative correlations between feather bacterial densities and components of plumage colouration as found in previous studies (Shawkey et al 2009;Gunderson et al 2009;Kilgas et al 2012a).…”
mentioning
confidence: 85%
See 3 more Smart Citations